2019
DOI: 10.4103/ijo.ijo_2090_18
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone photography for screening amblyogenic conditions in children

Abstract: Purpose:To validate the smartphone photography as a screening tool for amblyogenic conditions in children.Methods:Children between 5 to 8 years attending eye out patient department (OPD) were photographed (by an optometrist) with a smartphone to capture their pupillary red reflexes followed by clinical examination by the principal investigator (PI). The PI on the basis of clinical examination identified children with significant amblyogenic conditions and, subsequently, two ophthalmologists independently categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…However, more studies need to be performed to investigate any correlation between early fundus findings and final visual impairment. Smartphone photography for the detection of amblyogenic conditions in children 5-8 years of age, through snaps of pupillary red reflexes, was the objective of Gupta et al [ 45 ] trial. All high refractive errors were detected with success, however, moderate errors revealed false negative results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more studies need to be performed to investigate any correlation between early fundus findings and final visual impairment. Smartphone photography for the detection of amblyogenic conditions in children 5-8 years of age, through snaps of pupillary red reflexes, was the objective of Gupta et al [ 45 ] trial. All high refractive errors were detected with success, however, moderate errors revealed false negative results.…”
Section: Resultsmentioning
confidence: 99%
“…However, the contribution of RRT in pediatric visual screening could be more promising in the future. New technologies based on red reflex may improve RRT’s weak points[ 38 , 45 , 53 ]. Further investigation of these new devices and development of appropriate software is required in order to improve RRT accuracy on pediatric ocular diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the accuracy of smartphones for photorefractive screening [30,53,54]. Gupta et al [53] utilized smartphone photography to screen for amblyogenic factors and found that all high refractive errors ≥5 D were successfully detected, although moderate refractive errors (3.25-5.00 D) revealed false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the accuracy of smartphones for photorefractive screening [30,53,54]. Gupta et al [53] utilized smartphone photography to screen for amblyogenic factors and found that all high refractive errors ≥5 D were successfully detected, although moderate refractive errors (3.25-5.00 D) revealed false negatives. However, the authors excluded low refractive errors due to the red reflex appearing normal, and the total number of subjects with a moderate or high refractive error was only 22, thereby limiting the applicability of their results.…”
Section: Discussionmentioning
confidence: 99%
“…Modern technologies are being increasingly applied. Smart phones can be used to provide convenient and effective eye screening for children [ 8 , 9 ].…”
mentioning
confidence: 99%